Genome-wide identification, expression analysis, and response to abiotic stress of the phosphate transporter gene family in cucumber (Cucumis sativus L.) - Kunhao Xie; Mintao Sun; Xiaoqin Wang; Xiaoya Zhou; Qinghua Di; Yang Li; Guoxiu Wu; Yansu Li; Chaoxing He; Shengli Li (BMC Plant Biology)
Abstract Background Phosphorus (P) is an essential nutrient for plant growth and development, which plays a pivotal role in energy metabolism, signal transduction, and stress responses. However, approximately one-third of the world’s arable soils have insufficient available phosphorus, severely limiting crop productivity. While their genetic characteristics have been extensively studied in various plant species, the specific roles of phosphate transporter (PHT) in cucumber remain largely unexplored. Results In this study, 17 CsPHT genes were systematically identified in the cucumber genome and classified into four subfamilies: CsPHT1, CsPHT2, CsPHT3, and CsPHO1. Analyses of physicochemical properties and structural features revealed distinct divergence among subfamilies in terms of physicochemical characteristics, conserved domains, motif composition, and tertiary structure, whereas members within the same subfamily exhibited marked structural conservation. Collinearity analysis indicated that tandem duplication served as the primary driving force behind the expansion of the CsPHT gene family. Cis-regulatory element analysis showed that the promoter regions of CsPHT genes contained diverse cis-regulatory elements involved in stress response, hormonal regulation, and developmental processes. Expression profiling further revealed that several CsPHT genes, including CsPT1-3, CsPT1-4, CsPT1-7, CsPT1-9, CsPT1-11, CsPT2-1, and CsPHO1-3B, exhibited tissue-specific expression patterns in roots, leaves, and flowers. Among them, CsPT1-9, CsPT1-11, and CsPT2-1 were consistently induced under multiple abiotic stress conditions, indicating potential roles in abiotic stress responses in cucumber. In contrast, CsPT1-3 was downregulated under all abiotic stress treatments but was markedly upregulated in response to phytohormone treatments, suggesting a possible involvement in hormone-mediated phosphate acquisition from the soil. Conclusion This study conducted a systematic analysis of the CsPHT gene family, which provides a theoretical foundation and candidate genes for subsequent functional characterization and the genetic improvement of abiotic stress tolerance in cucumber.